B.P. Wham B.P. Wham - B.P. Wham; S. Dashti; K. Franke; R. Kayen; N.K. Oettle (Lowland Technology International, 2017)
Widespread damage to lifeline systems occurred as a result from the Kumamoto Earthquakes that initiated on April 14, 2016. Interruption to the water, gas, and electric power supply affected thousands of people. Landslides and surface rupture caused significant damage to transportation systems, especially roads and bridges. This paper provides an overview of observations and information gathered by US researchers (sponsored by Geotechnical Extreme Events Reconnaissance Association), Japanese researchers, and others regarding water supply damage. Emphasis is placed on the largest water authority in the region of the earthquake, Kumamoto City, including damage metrics for various pipe materials and diameters. The greatest damage occurred at valves and other fundamental mechanisms of large diameter pipelines. Pipelines constructed of ERDIP and HDPE performed most favorably while steel and cast iron pipelines were shown to be the more vulnerable. A liquefaction-induced lateral spreading site at which pipeline damage occurred is identified for further study.